2010
DOI: 10.1111/j.1365-2362.2010.02427.x
|View full text |Cite
|
Sign up to set email alerts
|

M-specific reverse transcription loop-mediated isothermal amplification for detection of pandemic (H1N1) 2009 virus

Abstract: This is an accurate and fast analysis system suitable for general diagnostic laboratories with only limited equipment, e.g. first-line health care centre. This assay will help clinicians and public health officials to react effectively during an outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that although multiplex nucleic acid detection tests have the advantage of high efficiency, due to the mutual interference of multiple primers, the analytic sensitivities of these assays tend to decrease. However, through the signal amplification effects of invader techniques and gold nanoparticle probe techniques, the sensitivity of the mRT-LAMP-IRNH assay established in this study was equivalent or even significantly increased as compared to general monoplex LAMP method23434445. In this study, the detection limit for A/H5 obtained by mRT-LAMP-IRNH was ten times higher than that obtained by real-time turbidity detection, indicating the cascade invasive reaction coupled with AuNPs hybridization increased the sensitivity of LAMP whose results were usually analyzed through turbidity.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies have shown that although multiplex nucleic acid detection tests have the advantage of high efficiency, due to the mutual interference of multiple primers, the analytic sensitivities of these assays tend to decrease. However, through the signal amplification effects of invader techniques and gold nanoparticle probe techniques, the sensitivity of the mRT-LAMP-IRNH assay established in this study was equivalent or even significantly increased as compared to general monoplex LAMP method23434445. In this study, the detection limit for A/H5 obtained by mRT-LAMP-IRNH was ten times higher than that obtained by real-time turbidity detection, indicating the cascade invasive reaction coupled with AuNPs hybridization increased the sensitivity of LAMP whose results were usually analyzed through turbidity.…”
Section: Discussionmentioning
confidence: 75%
“…(WHO 2009a ) or by designing infl uenza A virus consensus RT-LAMP assay primers and performing the two RT-LAMP assays together. Based on above facts and data, there is an urgent need for the development of an easy, accurate, and simple method for the diagnosis of this novel pandemic virus (Lee et al 2010 ). Lee et al ( 2010 ) developed M-specifi c reverse transcription loop-mediated isothermal amplifi cation for detection of pandemic (H1N1) 2009 virus.…”
Section: Human Virusesmentioning
confidence: 99%
“…Based on above facts and data, there is an urgent need for the development of an easy, accurate, and simple method for the diagnosis of this novel pandemic virus (Lee et al 2010 ). Lee et al ( 2010 ) developed M-specifi c reverse transcription loop-mediated isothermal amplifi cation for detection of pandemic (H1N1) 2009 virus. Based on validation by virus isolation, the specifi city and sensitivity of this M-specifi c RT-LAMP assay were 100 % and 98.25 %, respectively.…”
Section: Human Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…87,88 LAMP has successfully been applied to the rapid and real-time detection of common and emerging respiratory viral pathogens, including SARS-CoV 85,89 and the recently emerged novel A/H1N1. [90][91][92] RT-LAMP was used to detect Flu-A viruses covering H1 to H3. 77 Another similar RT-LAMP assay was described more recently that detects Flu-A virus H1 and H3 subtype strains and Flu-B virus strains.…”
Section: Loop-mediated Isothermal Amplificationmentioning
confidence: 99%